Rare chronic stridor: case report and literature review (2017)
This paper reports the case of a toddler with chronic stridor of four months of evolution, treated several times by micro-nebulization (MNB) with beta 2, adrenergics, O2 and corticosteroids with partial improvement. The patient did not have complementary studies nor a clear history of foreign body aspiration (FB). During the last visit to the ER, a neck X-ray revealed a stippling sign in the upper airway. A bronchoscopy was performed, and a sharp foreign body (fishbone) was found in the upper airway, which was subsequently removed. This case is reported due to the unusual evolution of the foreign body in the upper airway, which manifested as a chronic stridor that resolved without further complications.